Low anterior resection syndrome (LARS) in ovarian cancer patients - A multi-centre comparative cohort study. (June 2020) - Harpain, Felix; Kranawetter, Marlene; Zott, Tobias; Lazaridis, Ioannis I.; Guenin, Marc-Olivier; Ninkovic, Marijana; Kronberger, Irmgard E.; Tapiolas, Ingrid; Basany, Eloy Espin; Dauser, Bernhard; Herbst, Friedrich; Koh, Cherry; et al.
Abstract: Background: Low anterior resection syndrome (LARS) is a common functional disorder after low anterior resection impacting the quality of life. Data on LARS derives nearly exclusively from rectal cancer studies. Therefore, the study was designed to assess LARS in advanced epithelial ovarian cancer (EOC) patients, who underwent rectal resection and to compare it with a female rectal cancer cohort. Material and methods: A cross-sectional multi-centre analysis was performed on female patients suffering from either rectal or EOC who received a low anterior resection as part of their therapy regimen. None of the patients received pre- or postoperative radiotherapy. LARS was defined by using the validated LARS score and its severity was divided into "no", "minor" and "major LARS". Results: In total, 125 female patients (44.8% (n = 56) EOC vs. 55.2% (n = 69) rectal cancer patients) met the final inclusion criteria and were retrospectively analyzed. Baseline characteristics were comparable between the groups. Median follow-up was 22 (IQR 12–56) months. In total, 30.4% (n = 38) of the patient group reported bowel dysfunction after surgery. Rates of LARS were not significantly different between EOC and rectal cancer patients (major LARS 16.1% (n = 9) vs. 15.9% (n = 11); minor LARS 17.9% (n = 10) vs. 11.6% (n = 8); p = 0.984). The time interval between surgery and final assessment had no impact on the postoperative bowel function (p = 0.820). Conclusion: LARS is a frequent and highly underreported postoperative disorder in EOC patients who require cytoreductive surgery with rectal resection. The functional outcome is comparable to female patients with rectal cancer who underwent low anterior resection without receiving radiotherapy. Highlights: LARS is a common postoperative complication in ovarian cancer patients. LARS rates in ovarian and rectal cancer patients after rectal resection are comparable. The time interval between surgery and evaluation does not affect LARS prevalence.